A Correlation Self-Efficacy with Biology Students Participation in Waste Processing - Azhar, Dwi Yunar; Miarsyah, Mieke; Heryanti, Erna (Biosfer: Jurnal Pendidikan Biologi, 2015)
Jakarta residents’ waste volume increased twofoldon 2015.If the waste is negligible, there will beaccumulation ofwastewhich in turn damage the environmentandharm thesurrounding community. That requires participation in processing waste in the community, including biology students. One of the factors that can affect participation of biology students in processing waste is their self-efficacy. The aims of this study is to determine the correlation between self-efficacy with participation of biology students in processing waste. The research was conducted at State University of Jakarta on May 2015. Survey method with correlational studies used in this research, andit took 116 biology students which were taken by simple random sampling. after prerequisites was tested, it was found that data of this research was nomally distributed and homogeneous. The simple regression equation is Ŷ = 35,04 + 0,74X. Correlation coefficient obtained is 0,68 which means that there is a correlation between self-efficacy with participation of biology students in waste processing. Self-efficacy biology students contributed a total of 46.11% in the participation of waste management.